Evaluasi Teknis Sistem Penyangga Berdasarkan Metode RMR-System Pada Lubang D-25 L3 Tambang Batubara Bawah Tanah PT. Dasrat Sarana Arang Sejati (PT. DSAS), Kota Sawahlunto, Sumatera Barat. - Aldo Surya Pratama; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2023)
The potential for instability that occurs in rock when digging opening underground will usually always require special handling which functions for two things, the safety of workers and the safety of equipment contained in the mine. This study aims to determine rock mass class, support strength value, opening safety factor and support safety factor, and recommendations for safe supports based on rock class and support dimensions. The weighting of rock mass classes is carried out using the RMR-System method based on Bieniawski 1989. This analysis is carried out by weighting rock values based on parameters: rock compressive strength values, rock quality designation values, discontinuity spacing values, discontinuity condition values, groundwater values , and the joint orientation value to the tunnel. The results of the analysis are rock mass class values, rock strength, failure potential, stand up time values, and support recommendations based on rock mass class values. From the results of theanalysis at 100 m progress from the canopy, class III (Fair Rock) results were obtained for the tunnel wall which was coal, and class II rock (Good Rock) for the roof rock which was siltstone. From the results of the analysis of the strength of the supporting wood based on the wood strength class, it was found that the supporting wood used by PT. DSAS is included in class III wood which has a wood bending strength value of 702.5 kg/cm2 and a wood compressive strength value of 412.5 kg/cm2. Actual FK caps and side posts in hole D-25 L3 PT.DSAS were 1.37 and 5.80 with an average support distance of 1.83 m. FK stamp is still categorized as unsafe because it is below 1.5, so a buffer evaluation is carried out with a buffer distance of 1.67 so that FK ≥ 1.5 is obtained.